Characterization of sexual abuse cases valued in the emergency services and outpatient consultation of a first-level hospital institution in the department of Cauca, 2007 - 2015 - Cerón Hernández, Gloria; Roa Torres, Sandra; Salcedo Cifuentes, Mercedes (Universidad y Salud, 2017)
Introduction: Sexual abuse affects millions of children and adolescents and it impacts on their physical and mental health. Objective: To characterize the cases of sexual abuse valued in the emergency services and external consultation of a hospital institution of first level in the department of Cauca between 2007 and 2015. Materials and methods: A descriptive, retrospective study of victims of sexual abuse attended in external consultation/emergencies was made. Temporal and sociodemographic variables of the victim/aggressor and the context where the event occurred were selected. The analysis was done in Epi Info. Measures of central tendency, dispersion, proportions and reasons were calculated. The relationship between variables was assessed by using the Fischer test. Results: 77% of the victims were women, 23% men, at ages between 2 to 16 years and 100% were students. The act was committed by a single aggressor. Besides, in 93.0% of the cases, the act was perpetrated by acquaintances, of whom 42.9% were family members. Conclusions: Despite the control and regulation measures, the results suggest that sexual abuse takes place at very early ages. The aggressor is almost always a commonly known person with consanguineous bond, which facilitates the perpetuation of the act towards the family nucleus through deceit, blackmail or threat.